Cisplatin induced Mitochondrial DNA Damage In Dorsal Root Ganglion Neurons - Podratz, Jewel L. (2010)
Cisplatin is a platinum-based chemotherapeutic agent that induces peripheral neuropathy in 30% of patients. Peripheral neuropathy is the dose limiting side effect, which has no preventative therapy. We have previously shown that cisplatin induces apoptosis in dorsal root ganglion (DRG) sensory neurons by covalently binding to nuclear DNA (nDNA), resulting in DNA damage, subsequent p53 activation and Bax-mediated apoptosis via the mitochondria. We now demonstrate that cisplatin also directly binds to mitochondrial DNA (mtDNA) with the same binding affinity as nDNA. Cisplatin binds 1 platinum molecule per 2166 mtDNA base pairs and 1 platinum molecule per 3800 nDNA base pairs. Furthermore, cisplatin treatment inhibits mtDNA replication as detected by 5-bromo-2'-deoxy-uridine (BrdU) incorporation and inhibits transcription of mitochondrial genes. The relative reduction in mtDNA transcription is directly related to the distance the gene is located from the transcription initiation point, which implies that randomly formed platinum adducts block transcription. Cisplatin treated DRG neurons exhibit mitochondrial vacuolization and degradation in vitro and in vivo. Taken together, this data suggests that direct mtDNA damage may provide a novel, distinct mechanism for cisplatin-induced neurotoxicity separate from the established nDNA damage pathway.